Estimating the Period Prevalence of Mothers Who Have Abortions: A Population Based Study of Inclusive Pregnancy Outcomes - James Studnicki; John W. Fisher; Tessa Longbons; David C. Reardon; Donna J. Harrison; Christopher Craver; Maka Tsulukidze; Ingrid Skop (SAGE Publishing, 2021)
Introduction: The prevalence of induced abortion among women with children has been estimated indirectly by projections derived from survey research. However, an empirically derived, population-based conclusion on this question is absent from the published literature. Objective: The objective of this study was to describe the period prevalence of abortion among all other possible pregnancy outcomes within the reproductive histories of Medicaid-eligible women in the U.S. Methods: A retrospective, cross-sectional, longitudinal analysis of the pregnancy outcome sequences of eligible women over age 13 from the 17 states where Medicaid included coverage of most abortions, with at least one identifiable pregnancy between 1999 and 2014. A total of 1360 pregnancy outcome sequences were grouped into 8 categories which characterize various combinations of the 4 possible pregnancy outcomes: birth, abortion, natural loss, and undetermined loss. The reproductive histories of 4,884,101 women representing 7,799,784 pregnancy outcomes were distributed into these categories. Results: Women who had live births but no abortions or undetermined pregnancy losses represented 74.2% of the study population and accounted for 87.6% of total births. Women who have only abortions but no births constitute 6.6% of the study population, but they are 53.5% of women with abortions and have 51.5% of all abortions. Women with both births and abortions represent 5.7% of the study population and have 7.2% of total births. Conclusion: Abortion among low-income women with children is exceedingly uncommon, if not rare. The period prevalence of mothers without abortion is 13 times that of mothers with abortion.